Occultia (Scilloideae, Asparagaceae), a new genus from Malawi and Mozambique - Stedje, Brita; Rulkens, Antonius J.h.; Hankey, Andrew J. (Phytotaxa, 2022)
A new genus Occultia (Scilloideae, Asparagaceaae), is described from Malawi and Mozambique. One of the species on which this genus is based, was originally described as Hyacinthus. The genus is clearly separated from Ledebouria and closely related genera in characters of the flowers and the fruits. In Occultia tepals are united for 1/3 to ½ their length, the filaments are very short and inserted at the top of the perianth tube. In the fruiting stage, the tepals of the new genus become membranous and detached from their basis, but may form a cap on the developing capsule. In Ledebouria the tepals are free or united just at the base, the filaments are of a certain length and inserted at the base of the tepals. If persisting at fruiting stage the tepals are attached to the base of the capsule, and may become fleshy with time. The new genus comprises two species O. hyacinthoides and O. fragrans.